Removal of Pb2+ ions from contaminated solutions by microbial composite: Combined action of a soilborne fungus Mucor plumbeus and alunite matrix - Akar, Tamer; Celik, Sema; Ari, Asli Gorgulu; Akar, Sibel Tunali (ELSEVIER SCIENCE SA, 2013)
Mucor plumbeus-alunite composite was tested as a new sorbent material for the removal of Pb2+ ions from contaminated solutions. Sorption experiments were carried out by varying pH, contact time, sorbent dosage, initial metal ion concentration and flow rate. Zeta potential measurements, FTIR, SEM and EDX analyses were used to characterize the biosorption mechanism. The Pb2+ removal capacity of composite sorbent was significantly higher than that of M. plumbeus. The experimental results fitted satisfactory to the Langmuir isotherm in comparison to the Freundlich and Dubinin-Radushkevich model. Kinetic studies showed that the process followed the pseudo-second-order mechanism. The intraparticle diffusion played a significant role in first 40 and 50 min for M. plumbeus and composite sorbent, respectively. Reusability of composite material and Pb2+ recovery were investigated using acidic eluent. The presence of competing metal ions in the sorption medium reduced Pb2+ uptake potential of the composite sorbent material but it has still Pb2+ binding capacity in real wastewater conditions. Overall the results indicated that the prepared composite sorbent can be used as an effective and economic material for the environmental cleanup. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: M. plumbeus; Alunite; Lead sorption; Kinetic; Isotherm; AQUEOUS-SOLUTION; LEAD(II) IONS; WASTE BIOMASS; HEAVY-METALS; THERMODYNAMIC PARAMETERS; PSEUDOMONAS-AERUGINOSA; PB(II) BIOSORPTION; INDUSTRY WASTE; SILICA-GEL; EQUILIBRIUM; Engineering